Evaluation and comparison of the marginal adaptation of two different substructure materials - Karaman, Tahir; Ulku, Sabiha Zelal; Zengingul, Ali Ihsan; Guven, Sedat; Eratilla, Veysel; Sumer, Ebru (Korean Acad Prosthodontics, 2015)
PURPOSE. In this study, we aimed to evaluate the amount of marginal gap with two different substructure Materials using identical margin preparations. MATERIALS AND METHODS. Twenty stainless steel models with a chamfer were prepared with a CNC device. Marginal gap measurements of the galvano copings on these stainless steel models and Co-Cr copings obtained by a laser-sintering method were made with a stereomicroscope device before and after the cementation process and surface properties were evaluated by scanning electron microscopy (SEM). A dependent t-test was used to compare the mean of the two groups for normally distributed data, and two-way variance analysis was used for more than two data sets. Pearson's correlation analysis was also performed to assess relationships between variables. REAMS. According to the results obtained, the marginal gap in the galvano copings before cementation was measured as, on average, 24.47 +/- 5.82 mu m before and 35.11 +/- 6.52 mu m after cementation; in the laser-sintered Co-Cr structure, it was, on average, 60.45 +/- 8.87 mu m before and 69.33 +/- 9.03 mu m after cementation. A highly significant difference (P<.001) was found in marginal gap measurements of galvano copings and a significant difference (P<.05) was found in marginal gap measurements of the laser-sintered Co-Cr copings. According to the SEM examination, surface properties of laser sintered Co-Cr copings showed rougher structure than galvano copings. The galvano copings showed a very smooth surface. CONCLUSION. Marginal gaps values of both groups before and after cementation were within the clinically acceptable level. The smallest marginal gaps occurred with the use of galvano copings.
Keywords: Galvano crowns; Marginal adaptation; Laser sintered Co-Cr; Electroformed coping; Biocompatibility